MusE GAs FLOw and Wind (MEGAFLOW) IV. A two sightline tomography of a galactic wind. Issue 3 (31st December 2019) - Zabl, Johannes; Bouché, Nicolas F; Schroetter, Ilane; Wendt, Martin; Contini, Thierry; Schaye, Joop; Marino, Raffaella A; Muzahid, Sowgat; Pezzulli, Gabriele; Verhamme, Anne; Wisotzki, Lutz
ABSTRACT: Galactic outflows are thought to eject baryons back out to the circumgalactic medium. Studies based on metal absorption lines (Mg ii in particular) in the spectra of background quasars indicate that the gas is ejected anisotropically, with galactic winds likely leaving the host in a bi-conical flow perpendicular to the galaxy disc. In this paper, we present a detailed analysis of an outflow from a z = 0.7 'green-valley' galaxy [log ( M * /M⊙ ) = 9.8; SFR=0.5 M_ yr^-1 ] probed by two background sources from the MusE GAs FLOw and Wind (MEGAFLOW) survey. Thanks to a fortuitous configuration with a background quasar (SDSSJ1358 + 1145) and a bright background galaxy at z = 1.4, both at impact parameters of ≈\! 15 kpc, we can – for the first time – probe both the receding and approaching components of a putative galactic outflow around a distant galaxy. We measure a significant velocity shift between the Mg ii absorption from the two sightlines (84± 17 km s^-1 ), which is consistent with the expectation from our simple fiducial wind model, possibly combined with an extended disc contribution.